Fatigue of NiTi shape memory wires - Jaureguizahar, Sebastian Martin (2016)
In the present work, an innovative methodology for characterizing structural fatigue of NiTi superelastic wires is proposed. It consists in, firstly, performing low speed nearly isothermal pseudoelastic cycles in a limited region of the wire specimen. This results in the stabilization of the pseudooelastic behavior accompanied by a decrease in the stresses for forward and reverse transformations which allows obtaining an equivalent to a geometric dog-bone shaped specimen due to the reduced transformation stresses in the pre-cycled region. In a second stage, by limiting the transformation active zone to the pre-cycled region, the deformation speed can be increased to practical values avoiding any transformation activity outside that region. In that way, grip induced failures resulting in artificially shorter fatigue lives might be completely avoided thus allowing an accurate characterization of the true structural fatigue. Additionally, strain controlled experiments on wires in fully austenite and fully martensite states have been performed. Resulting fatigue lives in these cases were at least two orders of magnitude higher compared with the pseudoelastic fatigue indicating the decisive role played by the stress induced transformation in determining fatigue life. The influence of testing temperature and deformation rate on fatigue life has also been evaluated.